3x x 2)=45 2х-6х+5=45 -4х=45-5 -4х=40 -х=40:4 -х=10 х=-10 2) (26-6):2=20:2=10мин - едет на автобусе 10+6=16мин - идёт пешком 3) х - 2 сарай 3х- 1 сарай 3х-20=х+10 3х-х=10+20. 2х=30 х=30:2 x=15т - было во 2 сарае 15*3=45т - было в 1 сарае 4) 7х-(х+3)=3(2х-1) 7х-х-3=6х-3 7х-х-6х=-3+3 0х=0.x(x−3) = 0 x ( x - 3) = 0. If any individual factor on the left side of the equation is equal to 0 0, the entire expression will be equal to 0 0. x = 0 x = 0. x−3 = 0 x - 3 = 0. Set the first factor equal to 0 0. x = 0 x = 0. Set the next factor equal to 0 0 and solve. Tap for more steps... Set the next factor equal to 0 0.Решите уравнение (x-2)^4 + 3(x-2)^2 - 10 = 0. Решение.Now plot this, taking both branches of the square root into account. You might have to numerically solve the equation $x^{4/3}+4(1-x^2)=0$ in order to get the exact $x$-interval.Реши уравнение 19x+x-9x=11.решите уравнение (5x-2)(-x+3)=0.Steps Using Factoring By Grouping. 3 { x }^ { 2 } -x-2 = 0. 3 x 2 − x − 2 = 0. To solve the equation, factor the left hand side by grouping. First, left hand side needs to be rewritten as 3x^ {2}+ax+bx-2. To find a and b, set up a system to be solved. To solve the equation, factor the left hand side by grouping.3x^2. Natural Language; Math Input. Use Math Input Mode to directly enter textbook math notation. Try it. Also x with no exponent is the same as x 1. Here are some problems with answers that you should know based on what you learned on this page: 3x × 2x 2 = 6x 3 3x × 2x 3 = 6x 4 3x × 2x 4 = 6x 5 3x 2 × 2x = 6x 3 3x 2 × 2x 2 = 6x 4 3x 2 × 2x 3 = 6x 5 X times X Calculator For other numbers, go here for our popular "X times X Calculator.Compute answers using Wolfram's breakthrough technology & knowledgebase, relied on by millions of students & professionals. For math, science, nutrition, history ...plant city flea marketFree inequality calculator - solve linear, quadratic and absolute value inequalities step-by-step x^3-x^2-3x+2=0. Natural Language; Math Input; Extended Keyboard Examples Upload Random. Compute answers using Wolfram's breakthrough technology & knowledgebase, relied on by millions of students & professionals. For math, science, nutrition, history, geography, engineering, mathematics, linguistics, sports, finance, music…Therefore the required sum is 1/(1-x)^2 .9x2 − 4. View solution steps. Solution Steps. (3x-2) (3x+2) ( 3 x − 2) ( 3 x + 2) Multiplication can be transformed into difference of squares using the rule: \left (a-b\right)\left (a+b\right)=a^ {2}-b^ {2}. Multiplication can be transformed into difference of squares using the rule: ( a − b) ( a + b) = a 2 − b 2. \left (3x\right)^ {2 ...Apr 11, 2022 · Sold: 2 beds, 2 baths, 1260 sq. ft. condo located at 3720 Inverrary Dr Unit 3X, Lauderhill, FL 33319 sold for $162,700 on Apr 7, 2022. MLS# F10308247. Beautiful corner 2 bedroom 2 bath with spectac... Apr 11, 2022 · Sold: 2 beds, 2 baths, 1260 sq. ft. condo located at 3720 Inverrary Dr Unit 3X, Lauderhill, FL 33319 sold for $162,700 on Apr 7, 2022. MLS# F10308247. Beautiful corner 2 bedroom 2 bath with spectac... A lossless video/GIF/image upscaler achieved with waifu2x, Anime4K, SRMD and RealSR. Started in Hack the Valley 2, 2018.Free inequality calculator - solve linear, quadratic and absolute value inequalities step-by-step Решить уравнение: а). 6x3 - 24x= 0; б). 25x3- 10x2 +x =0; в). 2x4 + 6x3 - 8x2- 24x = 0; г). x5 - 2x4 + x3 - 8x2 + 16x... а). 6x^3 - 24x= 0 6x(x^2-4)=0 6x(x-2)(x+2)=0 6x=0 или x-2=0 или x+2=0 x=0 x=2 x=-2 Ответ:x=0 x=2 x=-2...patio umbrella 11 ftSo 3x times (5x-7) is (3x . 5x) plus (3x - 7). And we are multiplying the 2 times (5x-7) to give us these terms. But anyway, lets just multiply these out just to get our answer. 3x times 5x is same thing as (3 times 5) ( x times x) which is the same thing as 15x square. You can just do this x to the first time to x to the first. 2 Answers. George C. May 31, 2015. First notice that substituting x = 1 results in x3 −3x + 2 = 0. So (x −1) is a factor. Use synthetic division to find the remaining factor... x3 −3x + 2 = (x −1)(x2 +x −2) Notice that x = 1 is also a root of x2 + x −2.3x^2. Natural Language; Math Input. Use Math Input Mode to directly enter textbook math notation. Try it. x^3-x^2-3x+2=0. Natural Language; Math Input; Extended Keyboard Examples Upload Random. Compute answers using Wolfram's breakthrough technology & knowledgebase, relied on by millions of students & professionals. For math, science, nutrition, history, geography, engineering, mathematics, linguistics, sports, finance, music…Nghi N. May 29, 2015 No vertical asymptote, because (x^2 + 3) is always positive. Horizontal asymptote: y = 3 when x -> infinity. graph{(3x^2)/(x^2 + 3) [-10, 10, -5, 5]} Nghi N. May 29, 2015 No vertical asymptote, because (x^2 + 3) is always positive. Horizontal asymptote: y = 3 when x -> infinity. graph{(3x^2)/(x^2 + 3) [-10, 10, -5, 5]} Algebra Examples. Popular Problems. Algebra. Factor 3x-2. 3x − 2 3 x - 2. 3x−2 3 x - 2.Оперативная память Patriot Memory Viper Elite II 16 Гб (8 ГБ x 2).x^2 + 3x - 1. Natural Language; Math Input; Extended Keyboard Examples Upload Random. Compute answers using Wolfram's breakthrough technology & knowledgebase, relied on by millions of students & professionals. For math, science, nutrition, history, geography, engineering, mathematics, linguistics, sports, finance, music…x2+3x+2=0 Two solutions were found : x = -1 x = -2 Step by step solution : Step 1 :Trying to factor by splitting the middle term 1.1 Factoring x2+3x+2 The first term is, x2 its ... lifeproof iphone 8 plusSimple and best practice solution for F(x)=3x^2+3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.Algebra Examples. Popular Problems. Algebra. Factor 3x-2. 3x − 2 3 x - 2. 3x−2 3 x - 2.x^3-x^2-3x+2=0. Natural Language; Math Input; Extended Keyboard Examples Upload Random. Compute answers using Wolfram's breakthrough technology & knowledgebase, relied on by millions of students & professionals. For math, science, nutrition, history, geography, engineering, mathematics, linguistics, sports, finance, music…[math]\begin{array}{l}\log_22^{x-2}=\log_23^{(x-2)(x+4)}\\(x-2)\log_22=(x-2)(x+4)\log_23\\(x-2)(1-(x+4)\log_23)=0\\x=2;\;x=\log_32-4\end{array}[/math]. б) [math]2\in(0;3\rbrack[/math] [math]0<\log_32;\;\log_32-4\not\in\;(0;3\rbrack[/math].x^3-x^2-3x+2=0. Natural Language; Math Input; Extended Keyboard Examples Upload Random. Compute answers using Wolfram's breakthrough technology & knowledgebase, relied on by millions of students & professionals. For math, science, nutrition, history, geography, engineering, mathematics, linguistics, sports, finance, music…Solution for x^2-3x-2=0 equation: Simplifying x 2 + -3x + -2 = 0 Reorder the terms: -2 + -3x + x 2 = 0 Solving -2 + -3x + x 2 = 0 Solving for variable 'x'. Begin completing the square. Move the constant term to the right: Add '2' to each side of the equation. -2 + -3x + 2 + x 2 = 0 + 2 Reorder the terms: -2 + 2 + -3x + x 2 = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -3x + x 2 = 0 + 2 -3x + x 2 ...Answer (1 of 6): The area = length * Width. We know the width = X+6 inches and Area = x^3+3x^2–18x. This problem can be solved just by dividing the area by width ... Steps Using Factoring By Grouping. 3 { x }^ { 2 } -x-2 = 0. 3 x 2 − x − 2 = 0. To solve the equation, factor the left hand side by grouping. First, left hand side needs to be rewritten as 3x^ {2}+ax+bx-2. To find a and b, set up a system to be solved. To solve the equation, factor the left hand side by grouping. [math]\begin{array}{l}\log_22^{x-2}=\log_23^{(x-2)(x+4)}\\(x-2)\log_22=(x-2)(x+4)\log_23\\(x-2)(1-(x+4)\log_23)=0\\x=2;\;x=\log_32-4\end{array}[/math]. б) [math]2\in(0;3\rbrack[/math] [math]0<\log_32;\;\log_32-4\not\in\;(0;3\rbrack[/math].the spring league 2021Решите иррациональное неравенство √(x+5) - √(2x+3) > √(x-3).Now plot this, taking both branches of the square root into account. You might have to numerically solve the equation $x^{4/3}+4(1-x^2)=0$ in order to get the exact $x$-interval.Algebra. Simplify 3x (x-2) 3x(x − 2) 3 x ( x - 2) Apply the distributive property. 3x⋅x+3x⋅−2 3 x ⋅ x + 3 x ⋅ - 2. Multiply x x by x x by adding the exponents. Tap for more steps... Move x x. 3 ( x ⋅ x) + 3 x ⋅ − 2 3 ( x ⋅ x) + 3 x ⋅ - 2. Algebra 2 for Dummies, printable simultaneous equations, solving 3rd order for x, pizzazz math answers. Maths gcse algebra rule, examples of Math Trivia, 8th grade diamond problem, double integrals on ti89 calculator. X² -2x +√(2-x) = √(2-x) +3 ОДЗ: 2-х≥0 -х≥ -2 х≤2 x² -2x +√(2-x) - √(2-x) -3 =0 x² -2x -3=0 D=4 - 4* (-3) = 4+12=16 x₁= 2-4 = -1 2 x₂= 2+4 = 3 - не подходит по ОДЗ.Now plot this, taking both branches of the square root into account. You might have to numerically solve the equation $x^{4/3}+4(1-x^2)=0$ in order to get the exact $x$-interval.Simple and best practice solution for f(x)=4+3x-x^2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.решите уравнение (5x-2)(-x+3)=0.looking after synonymSimple and best practice solution for f(x)=4+3x-x^2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.Feb 12, 2018 · Best Answer. First one: (3X^2 +5) (x-2) = 3x^3 - 6x^2 +5x - 10. Second one is written incorrectly, I think you meant f/g (x) f (x) = 2x^2-5x-3 = (2x+1) (x-3) then f/g = (2x+1) (x-3) / (x) (2x +1) x cannot equal 0 or -1/2 because the denominator would be ZERO. Simplify to (x-3)/x (the (2x+1)'s 'cancel out') 3x^2. Natural Language; Math Input. Use Math Input Mode to directly enter textbook math notation. Try it. Условие. Решите уравнение: 1) x^3 − x = 0; 2) x^4 + x^2 = 0; 3) x^4 − 8x^3 = 0; 4) 49x^3 + 14x^2 + x = 0; 5) x^3 + x^2 − x − 1 = 0; 6) x^3 − 4x^2 − 25x + 100 = 0.Условие. Решите уравнение: 1) x^3 − x = 0; 2) x^4 + x^2 = 0; 3) x^4 − 8x^3 = 0; 4) 49x^3 + 14x^2 + x = 0; 5) x^3 + x^2 − x − 1 = 0; 6) x^3 − 4x^2 − 25x + 100 = 0.Algebra. Simplify 3x (x-2) 3x(x − 2) 3 x ( x - 2) Apply the distributive property. 3x⋅x+3x⋅−2 3 x ⋅ x + 3 x ⋅ - 2. Multiply x x by x x by adding the exponents. Tap for more steps... Move x x. 3 ( x ⋅ x) + 3 x ⋅ − 2 3 ( x ⋅ x) + 3 x ⋅ - 2.∭ V x 2 d x d y d z , V : x 2 + y 2 + z 2 = R 2 , z ≥ 0 , x > 0. ∭ V x 2 d x d y d z , V : x 2 + y 2 = x , z = x 2 + y 2 , z = 0.Solution for x^2-3x-2=0 equation: Simplifying x 2 + -3x + -2 = 0 Reorder the terms: -2 + -3x + x 2 = 0 Solving -2 + -3x + x 2 = 0 Solving for variable 'x'. Begin completing the square. Move the constant term to the right: Add '2' to each side of the equation. -2 + -3x + 2 + x 2 = 0 + 2 Reorder the terms: -2 + 2 + -3x + x 2 = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -3x + x 2 = 0 + 2 -3x + x 2 ...3x^2. Natural Language; Math Input. Use Math Input Mode to directly enter textbook math notation. Try it. Dec 19, 2021 · 3x leveraged ETFs look to generate three times the returns of the underlying index. This also means 3x leveraged ETFs also will generate losses that are three times that of the index. It's also key to know that the return is expected on the daily return, not the annual return. 3x leveraged ETFs are often not considered wise long-term investments. Free inequality calculator - solve linear, quadratic and absolute value inequalities step-by-step Apr 8, 2015. To find x, we first have to factorize the equation. x2 −3x = 0. As x is the common factor between the 2 values, we factorize the equation by taking x out of x2 − 3x = 0. x2 −3x = 0. x(x −3) = 0. Any value that is multiplied by 0, will give 0 as the answer. 1x0=0.Factor out the Greatest Common Factor (GCF), '3x'. 3x(2 + -3x + x 2) = 0 Factor a trinomial. 3x((1 + -1x)(2 + -1x)) = 0 Ignore the factor 3. Subproblem 1 Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0 Subproblem 2Also x with no exponent is the same as x 1. Here are some problems with answers that you should know based on what you learned on this page: 3x × 2x 2 = 6x 3 3x × 2x 3 = 6x 4 3x × 2x 4 = 6x 5 3x 2 × 2x = 6x 3 3x 2 × 2x 2 = 6x 4 3x 2 × 2x 3 = 6x 5 X times X Calculator For other numbers, go here for our popular "X times X Calculator.Solution. Verified by Toppr. In the given polynomial 3x 2−x−4, The first term is 3x 2 and its coefficient is 3. The middle term is −x and its coefficient is −1. The last term is a constant term −4. Multiply the coefficient of the first term by the constant 3×−4=−12. We now find the factor of −12 whose sum equals the coefficient ...3X (2018) Close. 1 of 1. 3X (2018) 1 of 1. 3X (2018) Titles 3X. Languages English ... suffolk county covid casesA lossless video/GIF/image upscaler achieved with waifu2x, Anime4K, SRMD and RealSR. Started in Hack the Valley 2, 2018.[math]\begin{array}{l}\log_22^{x-2}=\log_23^{(x-2)(x+4)}\\(x-2)\log_22=(x-2)(x+4)\log_23\\(x-2)(1-(x+4)\log_23)=0\\x=2;\;x=\log_32-4\end{array}[/math]. б) [math]2\in(0;3\rbrack[/math] [math]0<\log_32;\;\log_32-4\not\in\;(0;3\rbrack[/math].-5(x+0,3)+2(11-3x)при x=0,2.2/3x - Wolfram|Alpha. Area of a circle? Easy as pi (e). Unlock Step-by-Step. Natural Language. Math Input. Use Math Input Mode to directly enter textbook math notation.Решите иррациональное неравенство √(x+5) - √(2x+3) > √(x-3).Steps Using Factoring By Grouping. 3 { x }^ { 2 } -x-2 = 0. 3 x 2 − x − 2 = 0. To solve the equation, factor the left hand side by grouping. First, left hand side needs to be rewritten as 3x^ {2}+ax+bx-2. To find a and b, set up a system to be solved. To solve the equation, factor the left hand side by grouping.Steps Using Factoring By Grouping. 3 { x }^ { 2 } -x-2 = 0. 3 x 2 − x − 2 = 0. To solve the equation, factor the left hand side by grouping. First, left hand side needs to be rewritten as 3x^ {2}+ax+bx-2. To find a and b, set up a system to be solved. To solve the equation, factor the left hand side by grouping.Algebra Examples. Popular Problems. Algebra. Factor 3x-2. 3x − 2 3 x - 2. 3x−2 3 x - 2.)=45 2х-6х+5=45 -4х=45-5 -4х=40 -х=40:4 -х=10 х=-10 2) (26-6):2=20:2=10мин - едет на автобусе 10+6=16мин - идёт пешком 3) х - 2 сарай 3х- 1 сарай 3х-20=х+10 3х-х=10+20. 2х=30 х=30:2 x=15т - было во 2 сарае 15*3=45т - было в 1 сарае 4) 7х-(х+3)=3(2х-1) 7х-х-3=6х-3 7х-х-6х=-3+3 0х=0.Factor out the Greatest Common Factor (GCF), '3x'. 3x(2 + -3x + x 2) = 0 Factor a trinomial. 3x((1 + -1x)(2 + -1x)) = 0 Ignore the factor 3. Subproblem 1 Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0 Subproblem 2x2+3x+2=0 Two solutions were found : x = -1 x = -2 Step by step solution : Step 1 :Trying to factor by splitting the middle term 1.1 Factoring x2+3x+2 The first term is, x2 its ... 2/3x - Wolfram|Alpha. Area of a circle? Easy as pi (e). Unlock Step-by-Step. Natural Language. Math Input. Use Math Input Mode to directly enter textbook math notation.x2+3x+2=0 Two solutions were found : x = -1 x = -2 Step by step solution : Step 1 :Trying to factor by splitting the middle term 1.1 Factoring x2+3x+2 The first term is, x2 its ... project x zone 3Решите уравнение x^2-12/x-3=x/3-x. Алгебра.x2+3x+2=0 Two solutions were found : x = -1 x = -2 Step by step solution : Step 1 :Trying to factor by splitting the middle term 1.1 Factoring x2+3x+2 The first term is, x2 its ... Решите уравнение 5x-(3+2x-2x²) = 2x²-7x+17.Therefore the required sum is 1/(1-x)^2 .A stripper, janitor and lawyer are found dead in a shopping mall and a crazed religious fanatic is behind it all. Find out why and how this went down in 3X. Directors Logan Bennett Leigh Takata Writer Leigh Takata Stars Leigh Takata Ingrid Jordan Heather Rhea See production, box office & company info Photos Add photo Top cast Leigh TakataX² -2x +√(2-x) = √(2-x) +3 ОДЗ: 2-х≥0 -х≥ -2 х≤2 x² -2x +√(2-x) - √(2-x) -3 =0 x² -2x -3=0 D=4 - 4* (-3) = 4+12=16 x₁= 2-4 = -1 2 x₂= 2+4 = 3 - не подходит по ОДЗ.Simplify (3x)^2. (3x)2 ( 3 x) 2. Apply the product rule to 3x 3 x. 32x2 3 2 x 2. Raise 3 3 to the power of 2 2. 9x2 9 x 2.Simple and best practice solution for f(x)=4+3x-x^2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.Решите уравнение (x-2)^4 + 3(x-2)^2 - 10 = 0. Решение.∭ V x 2 d x d y d z , V : x 2 + y 2 + z 2 = R 2 , z ≥ 0 , x > 0. ∭ V x 2 d x d y d z , V : x 2 + y 2 = x , z = x 2 + y 2 , z = 0.= x X∞ k=0 x2 3 k = x 1−(x2/3) = 3x 3−x2 for |x2/3| < 1. 1.2 Radius of Convergence Radius of Convergence There are exactly three possibilities for a power ... how much does an oil change cost at jiffy lube∭ V x 2 d x d y d z , V : x 2 + y 2 + z 2 = R 2 , z ≥ 0 , x > 0. ∭ V x 2 d x d y d z , V : x 2 + y 2 = x , z = x 2 + y 2 , z = 0.Therefore the required sum is 1/(1-x)^2 .Решите уравнение x^2-2x+ (корень2-x) = (корень2-x) +3.3X (2018) Close. 1 of 1. 3X (2018) 1 of 1. 3X (2018) Titles 3X. Languages English ... Algebra Examples. Popular Problems. Algebra. Factor 3x-2. 3x − 2 3 x - 2. 3x−2 3 x - 2.Algebra. Simplify 3x (x-2) 3x(x − 2) 3 x ( x - 2) Apply the distributive property. 3x⋅x+3x⋅−2 3 x ⋅ x + 3 x ⋅ - 2. Multiply x x by x x by adding the exponents. Tap for more steps... Move x x. 3 ( x ⋅ x) + 3 x ⋅ − 2 3 ( x ⋅ x) + 3 x ⋅ - 2. x^2 + 3x - 1. Natural Language; Math Input; Extended Keyboard Examples Upload Random. Compute answers using Wolfram's breakthrough technology & knowledgebase, relied on by millions of students & professionals. For math, science, nutrition, history, geography, engineering, mathematics, linguistics, sports, finance, music…Then type x=6. Try it now: 2x+3=15 @ x=6 Clickable Demo Try entering 2x+3=15 @ x=6 into the text box. After you enter the expression, Algebra Calculator will plug x=6 in for the equation 2x+3=15: 2(6)+3 = 15. The calculator prints "True" to let you know that the answer is right. More ExamplesПример : Упростить выражение 4x2−9y2x:2x−3y5x+xy.x^3-x^2-3x+2=0. Natural Language; Math Input; Extended Keyboard Examples Upload Random. Compute answers using Wolfram's breakthrough technology & knowledgebase, relied on by millions of students & professionals. For math, science, nutrition, history, geography, engineering, mathematics, linguistics, sports, finance, music…Simplify (3x)^2. (3x)2 ( 3 x) 2. Apply the product rule to 3x 3 x. 32x2 3 2 x 2. Raise 3 3 to the power of 2 2. 9x2 9 x 2.x^2 + 3x - 1. Natural Language; Math Input; Extended Keyboard Examples Upload Random. Compute answers using Wolfram's breakthrough technology & knowledgebase, relied on by millions of students & professionals. For math, science, nutrition, history, geography, engineering, mathematics, linguistics, sports, finance, music…one piece wallpaper hdFree inequality calculator - solve linear, quadratic and absolute value inequalities step-by-step Steps Using Factoring By Grouping. 3 { x }^ { 2 } -x-2 = 0. 3 x 2 − x − 2 = 0. To solve the equation, factor the left hand side by grouping. First, left hand side needs to be rewritten as 3x^ {2}+ax+bx-2. To find a and b, set up a system to be solved. To solve the equation, factor the left hand side by grouping. x2+3x+2=0 Two solutions were found : x = -1 x = -2 Step by step solution : Step 1 :Trying to factor by splitting the middle term 1.1 Factoring x2+3x+2 The first term is, x2 its ... Модификация 3X, предназначенная для китайского рынка, отличается вариантом памяти 2/32 Гб. Обе версии работают под управлением MIUI на основе Android 6.0.1. Ссылки Algebra. Simplify 3x (x-2) 3x(x − 2) 3 x ( x - 2) Apply the distributive property. 3x⋅x+3x⋅−2 3 x ⋅ x + 3 x ⋅ - 2. Multiply x x by x x by adding the exponents. Tap for more steps... Move x x. 3 ( x ⋅ x) + 3 x ⋅ − 2 3 ( x ⋅ x) + 3 x ⋅ - 2. Apr 11, 2022 · Sold: 2 beds, 2 baths, 1260 sq. ft. condo located at 3720 Inverrary Dr Unit 3X, Lauderhill, FL 33319 sold for $162,700 on Apr 7, 2022. MLS# F10308247. Beautiful corner 2 bedroom 2 bath with spectac... Nghi N. May 29, 2015 No vertical asymptote, because (x^2 + 3) is always positive. Horizontal asymptote: y = 3 when x -> infinity. graph{(3x^2)/(x^2 + 3) [-10, 10, -5, 5]} Jawaban paling sesuai dengan pertanyaan Diketahui : g(x) = 3x-1 (fog)(x) = 9x 2 +6x+2 Maka f(x) =... Compute answers using Wolfram's breakthrough technology & knowledgebase, relied on by millions of students & professionals. For math, science, nutrition, history ...womens nike air jordans -fc